A Bayesian machine learning approach for drug target identification using diverse data types - Neel S. Madhukar (Nature Portfolio, 2019)
Drug target identification is a crucial step in drug development. Here, the authors introduce a Bayesian machine learning framework that integrates multiple data types to predict the targets of small molecules, enabling identification of a new set of microtubule inhibitors and the target of the anti-cancer molecule ONC201.